THE RELATIONSHIP BETWEEN THE INTAKE OF ANIMAL AND VEGETABLE PROTEIN AND STUNTING IN CHILDREN AGED 3-5 YEARS OLD IN PENAWANGAN VILLAGE, PRINGAPUS SUBDISTRICT, SEMARANG REGENCY - Agnes Setiana, Dwi; Maryanto, Sugeng; Mulyasari , Indri (UNIVERSITAS NGUDI WALUYO, 2015)
Stunting is one of the consequences that arises from a state of malnutrition that lasts a long time. One of the lack of nutrients is proteins. The deficit of intake of animal and vegetable protein will impact on growth. The aim of this study was known the relationship between the intake of animal and vegetable protein and stunting in children aged 3-5 years old in Penawangan Village, Pringapus Subdistrict, Semarang regency. This research was Correlational study with cross-sectional approach. The population in this study was all mothers and children aged 3-5 years old in Penawangan village, Pringapus subdistrict, Semarang regency. It obtained the samples of 64 children with proportional random sampling method. Data collecting used microtoise, bath room scales, and semi-quantitative FFQ. Bivariate analysis used spearman rho (Î±= 0,05). Most animal protein intake was in the category of severe deficit which was 39.1%, the category of moderate deficit which was 1.6%, the category of mild deficit which was 3.1%, the category of normal which was 37.5%, the category of over which was 18.8%. The intake of vegetable protein was mostly in the category of severe deficit which was 51.6%, the category of moderate deficit which was 32.8%, the category of mild deficit which was 14.1%, the category of normal which was 1.6%. The incidences of stunting were in 33 children (51.6%) and unstunting were in 31 children (48.4%). There was a relationship between the intake of animal protein with the incidences of stunting (p = 0.0001, r = 0.798). There was a relationship between the intake of vegetable protein with the incidences of stunting (p = 0.0001, r = 0.560). There was a relationship between the intake of animal and vegetable protein with stunting in children aged 3-5 years old in Penawangan village, Pringapus subdistrict, Semarang regency.